The Teacher’s Response in Relation to the Implementation of Simpler Game Used in Learning English Vocabulary - Safitri, Hilma; Veny Kurniasih; Zahara Marsellina Putri (Universitas Cokroaminoto Palopo, 2025)
This study aimed to find out the teachers' responses in relation to the implementation of a simpler game used at SMP Al-Mutazam Sepatan. This study is included in the descriptive qualitative study in accordance with what some researchers think might be the data qualification (Hamied, 2017). The participant involved was a teacher teaching English, particularly vocabulary in English. The data were collected by conducting some observations and an interview with the teacher involved in this study. The data were analyzed based on interpreted data analysis in which some data were concluded in term of words and phrases. Based on the data findings, it was found that the teacher had some statements such as (1) the simpler game benefits the students in learning English, particularly vocabulary English, and (2) some students may have some difficulties observing vocabulary knowledge. Therefore, they had to participate in learning by using the simpler game, and the last (3) a teacher should have some knowledge regarding how and why he or she provides the game in the classroom.